The Legal Construction of Electoral Crimes in the Indonesian Legislative Framework - Muhammad Fadel Kadir; Nur Fadhilah Mappaselleng; Askari Razak (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the legal construction of electoral crimes within the Indonesian legislative framework. Elections in Indonesia are constitutionally mandated to be conducted in a direct, general, free, secret, honest, and fair manner as stipulated in Article 22E of the 1945 Constitution. To safeguard these principles, various statutory regulations have been enacted, particularly Law No. 7 of 2017 on General Elections and Law No. 10 of 2016 on Regional Head Elections. This research employs a normative legal method with statutory, conceptual, and analytical approaches to analyze the formulation of electoral criminal norms, the structure of offenses, legal subjects, protected legal interests, and sanction mechanisms. The study finds that the regulation of electoral crimes has been systematically constructed through a multi-layered framework consisting of constitutional provisions, statutory regulations, general criminal law, and implementing regulations. However, several issues remain, including ambiguity in the formulation of offense elements, overlap between administrative, ethical, and criminal violations, limited regulatory reach over digital-based electoral offenses, and inconsistencies in sanction proportionality. These challenges affect the effectiveness of electoral law enforcement and the protection of fundamental electoral principles. Therefore, harmonization and reformulation of electoral criminal norms are necessary to ensure clearer offense elements, stronger legal certainty, and a sanction system that proportionally protects the integrity of electoral processes and democratic legitimacy in Indonesia